Peningkatan Pengetahuan Terhadap Pengelolaan Obat yang Tepat pada Masyarakat Kelurahan Candirenggo RW 07 Melalui Sosialisasi DAGUSIBU Obat - Maulida, Faradillah Laili; Salsabila, Agisha Salwa; Syahroni, Moch Ilham; Auliyansyah, Ach Afrian; Fadlilah, Rizki Laili; Priatmoko, Sigit (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
Some parts of our society are having problems with handling medicine properly. One of the causes is not all people understand how to heal their sickness with many kinds of medicine. Various medicine-society related problems can be caused by people's lack of understanding about the use and handling of medicine correctly. One way to inform society how to manage medicine properly is to implement the DAGUSIBU (DApatkan, GUnakan, SImpan, BUang). Based on the information obtained, residents of the Candirenggo sub-district have never received information about DAGUSIBU. That’s why it is necessary to socialize DAGUSIBU in their community. The purpose of this activity is to make them understand and share information about the correct way to receive, apply, install and waste the medicines among their family and their neighbor. The method used in this activity is through socialization or lectures, interactive discussions., and the distribution of DAGUSIBU brochures. The dissemination about DAGUSIBU went smoothly. The participants who attended were very enthusiastic in listening to explanations and actively asked questions regarding the use of medicine and their treatment. This can support the realization of government programs in improving health services for the community. This socialization increases participants' understanding of drug management properly, from this socialization, the participants suggested to apply the knowledge gained to their family and community environment properly and correctly.